Yeast derivatives and wheat germ in the adult diet modulates fecundity in a tephritid pest - Goane, Lucía; Pereyra, P. M.; Castro, F.; Ruiz, María Josefina; Juárez, María Laura; Segura, Diego Fernando; Vera, María Teresa (Cambridge University Press, 2019)
Anastrepha fraterculus (Wiedemann), a pest of great economic importance in South America, needs urgently to be controlled by environmentally friendly methods such as the sterile insect technique for which mass rearing of insects is required. Because oogenesis takes place during the adult stage, mass-rearing facilities should provide the females a diet that maximizes egg production at the lowest cost. Accordingly, we investigated the effect of artificial protein sources in the adult diet (yeast derivatives of different cost but with similar amino acids profiles, and the addition of wheat germ) on fecundity. Additionally, we evaluated different ratios of yeast derivatives or wheat germ on ovary maturation, fecundity, and fertility as well as their association with the nutrient content of females. Females fed hydrolyzed yeast and yeast extract attained the highest fecundity level, and those fed brewer's yeast the lowest. Reducing the amount of hydrolyzed yeast, an expensive protein source, in the diet negatively affected fecundity and ovary maturation. Increasing the amount of brewer's yeast, a low-cost protein source, did not favor fecundity. The addition of wheat germ in the adult diet improved fecundity regardless of the yeast derivate considered. Percentage of egg hatch was not affected by the diet. Nutrient content of A. fraterculus females varied according to the adult diet provided and mating status. Our findings provide novel baseline information to understand the role of nutrition on reproductive performance of A. fraterculus females and are discussed in the context of resource allocation. They also provide valuable advances in the search for cost-effective adult diets at fruit fly mass rearing facilities.